2011
DOI: 10.1093/humupd/dmr007
|View full text |Cite
|
Sign up to set email alerts
|

Is aspirin effective in women undergoing in vitro fertilization (IVF)? Results from an individual patient data meta-analysis (IPD MA)

Abstract: Aspirin does not improve pregnancy rates after IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
2
14
2
Order By: Relevance
“…The inclusion rate is adequate compared with other published IPD metaanalyses with inclusion rates of 12-24% 40,41 ; 1 study included 6 of 10 eligible studies that added up to an inclusion rate of 60%. 41 The number of IPD in our study on the other hand was much higher than in other IPDs, mostly containing several thousands of participants. [40][41][42] The reason for this is our inclusion of nationwide registry based studies.…”
Section: Strengths and Weaknessescontrasting
confidence: 53%
See 1 more Smart Citation
“…The inclusion rate is adequate compared with other published IPD metaanalyses with inclusion rates of 12-24% 40,41 ; 1 study included 6 of 10 eligible studies that added up to an inclusion rate of 60%. 41 The number of IPD in our study on the other hand was much higher than in other IPDs, mostly containing several thousands of participants. [40][41][42] The reason for this is our inclusion of nationwide registry based studies.…”
Section: Strengths and Weaknessescontrasting
confidence: 53%
“…41 The number of IPD in our study on the other hand was much higher than in other IPDs, mostly containing several thousands of participants. [40][41][42] The reason for this is our inclusion of nationwide registry based studies. Our combined database includes 99,415 women with a subsequent pregnancy, which is 69% of the 143,659 women who could be included in our regular metaanalysis of the 88 eligible studies.…”
Section: Strengths and Weaknessescontrasting
confidence: 53%
“…Two recent meta-analyses found that LDA had no significant effect on the clinical pregnancy rate(RR 1·03, 95% CI: 0·91, 1·17) or live birth rate (RR 0·91, 95% CI: 0·72, 1·15) in women undergoing IVF. 1920 A systematic review with less stringent quality criteria found that although pregnancy rates were increased with LDA (OR 1·19, 95% CI: 1·01, 1·39), live birth rates were not affected (OR 1·08, 95% CI: 0·82, 1·68). 21 Our study is the first and largest to show that LDA does not decrease pregnancy loss when initiated preconception among women with a history of only one to two prior pregnancy losses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta‐analyses assessing the efficacy of aspirin have shown apparently conflicting results [15,16,53]. Khairy et al.…”
Section: Discussionmentioning
confidence: 99%